Gender Differences in Cognitive Abilities Among the Elderly Poor of Peru - Novella, Rafael (2019)
We study gender differences on cognitive functioning among older adults living in poverty. The data come from the Survey of Health and Wellbeing of the Elderly (ESBAM) which is the baseline survey to evaluate the Peru’s social pension program Pension 65. The results show that females are better off than males regarding episodic memory, but worse off in mental intactness. We do not find gender differences in the overall measure of cognition, but regional differences matter in favour of urban localities. The sizeable associations of education and quality of childhood nutrition with later-life cognition confirm the long-term impacts of early life developments on current outcomes, particularly in the case of females. Therefore, policies aimed at improving early childhood development are expected to have a positive impact in the quality of old-age.